Everyday Life Residents of Almaty Region and City Dwellers in the Soviet Union from 1920 to the 1930s (State of Health Care) - Tazhieva, Saltanat; Kamshat, Rustem; Duman, Zhekenov; Marlan, Baizhanov; Askhat, Darkenbayev (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
This work studied everyday life of Almaty region dwellers and the impact on their life from rising socialisation and reform of state branches. The interest in everyday life is a result of making an effort to comprehend new construction samples from the period of Stalin’s first five-year plan from the point of view of a Soviet man/population? This information presented the ambitions and living conditions of Almaty’s residents in the industrialisation years of the Soviet Union’s history. During the 1930s, modernisation and its effects were one of the most important factors in the life of Almaty residents. This paper focusses on healthcare and quality of medical service in that era. The research has been done in Almaty city but the analysis have been taken for research from Almaty surrounding regions as well. Zhetisu regional hospital locates in Almaty region.